A Comparison of Diversifying and Nondiversifying Australian Industrial Firms - McDougal, Fred M.; Round, David K. (Academy of Management Journal, 1984)
This paper examines corporate motives for diversification and compares the performance of diversifying and nondiversifying Australian industrial firms. No significant difference appears to exist in the profitability of the two groups of companies, and little difference exists in the risk faced by the two groups. Profitability, however, does appear to be related to the extent of diversification.